The roles of fungus in CNS autoimmune and neurodegeneration disorders - Wu, Chuyu; Jiang, Mei-Ling; Jiang, Runqui; Pang, Tao; Zhang, Cun-Jin (Frontiers in Immunology, 2023)
Fungal infection or proliferation in our body is capable of initiation of strong inflammation and immune responses that result in different consequences, including infection-trigged organ injury and inflammation-related remote organ dysfunction. Fungi associated infectious diseases have been well recognized in the clinic. However, whether fungi play an important role in non-infectious central nervous system disease is still to be elucidated. Recently, a growing amount of evidence point to a non-negligible role of peripheral fungus in triggering unique inflammation, immune response, and exacerbation of a range of non-infectious CNS disorders, including Multiple sclerosis, Neuromyelitis optica, Parkinson’s disease, Alzheimer’s disease, and Amyotrophic lateral sclerosis et al. In this review, we summarized the recent advances in recognizing patterns and inflammatory signaling of fungi in different subsets of immune cells, with a specific focus on its function in CNS autoimmune and neurodegeneration diseases. In conclusion, the fungus is capable of triggering unique inflammation by multiple mechanisms in the progression of a body of CNS non-infectious diseases, suggesting it serves as a key factor and critical novel target for the development of potential therapeutic strategies.